Holistic Assessment and Ethical Disputation on a New Trend in Solid Biofuels - Hašková, Simona (Science and engineering ethics, 2017)
A new trend in the production technology of solid biof uels has appeared. There is a wide consensus that most solid biofuels will be produced according to the new production methods within a few years. Numerous samples were manufactured from agro-residues according to conventional methods as well as new methods. Robust analyses that reviewed the hygienic, environmental, financial and ethical aspects were performed. The hygienic and environmental aspect was assessed by robust chemical and technical analyses. The financial aspect was assessed by energy cost breakdown. The ethical point of view was built on the above stated findings, the survey questionnaire and critical discussion with the literature. It is concluded that the new production methods are significantly favourable from both the hygienic and environmental points of view. Financial indicators do not allow the expressing of any preference. Regarding the ethical aspect, it is concluded that the new methods are beneficial in terms of environmental responsibility. However, it showed that most of the customers that took part in the survey are price oriented and therefore they tend to prefer the cheaper-conventional alternative. In the long term it can be assumed that expansion of the new technology and competition among manufacturers will reduce the costs.
Keywords: Subsidy policy; Ethics; průzkumy a dotazníky; životní prostředí; Financial analysis; etika; Ethics in decision making; Biofuels; Economics; ekonomika; Environment; Surveys and Questionnaires; Cost breakdown; biopaliva